(untitled) (Bristol,Philadelphia, 1992)
This anthology presents the reader with a fascinating view of the whimsical side of science. A unique and historical collection of humorous stories, anecdotes, verse and cartoons touching every science has been meticulously compiled by the author from worldwide sources.
Keywords: Science,Khoa học; Humor,Hài hước